Proactive Reporting on Sustainable Development: Impacts on The Financial Perfomances of Some French Listed Companies - Cailliau, Florent (2006)
For more than 30 years, academic studies have focused on the financial impact of social and environmental performances of companies without finding any theory which does not suffer from ambiguity or instability, Allouche & Laroche, (2005); Gond, J.P. (2001); Margolis & Walsh, (2001a), (2003); Rowley & Berman, (2000). From a business perspective, sustainable companies are those that seek to minimize the environmental footprint of their operations, while simultaneously contributing to the economic and social development of the communities in which they operate internationally, Feltmate, B., Schofield, B. and Yachnin, R. (2001). As expressed by the concerns of Kofi Annan at the United Nations Millennium Summit in 2001, the Sustainable Development (SD) concept is now becoming a major issue for managers who are - in most cases - not entirely comfortable with the relationship between the financial and the intangible, Beckwith, N. (2004).